The “WEIRDEST” Organizations in the World? Assessing the Lack of Sample Diversity in Organizational Research - Schimmelpfennig, Robin; Elbæk, Christian; Mitkidis, Panagiotis; Singh, Anisha; Roberson, Quinetta (Journal of Management, 2025)
Sampling data from organizations and humans associated with those organizations is essential to organizational research. Much of what we know about organizations is based on such work. However, this empirical foundation may be compromised, calling into question the field’s theoretical and empirical findings. Studies often sample data from relatively similar, narrow contexts, so a lack of sample diversity accumulates in the discipline. To conceptualize this lack of sample diversity and examine its prevalence across research publications, we conduct a pre-registered systematic review of articles from 2018 to 2022 in six top management journals and another systematic review of articles from 2013 to 2022 in six additional journals (not pre-registered). Our review assesses sample country diversity while also exploring within-country factors that are relatively under or oversampled, such as the size or industry of the sampled organization. We find a lack of sample diversity, for instance, a strong bias toward WEIRD (Western, educated, industrialized, rich, and democratic) samples and an underrepresentation of small and medium-sized enterprises in organizational research. Based on the findings and past work, we introduce a conceptual framework for sample diversity along three dimensions: the sample’s geographical, organizational, and personnel contexts. Additionally, we discuss factors that contribute to a lack of sample diversity and propose guidelines for authors, reviewers, and editors to enhance it. Overall, this article seeks to improve the robustness and relevance of theoretical and empirical organizational research, thereby preventing the formulation of misinformed policies and practices in both organizational settings and broader societal contexts.